Production of Extracellular Protein a from a Methicillin-Resistant Strain of Staphylococcus Aureus - Tahir, Sharifah (1994)
Protein A was produced extra cellularly by methicillinresistant Staphylococcus aureus, strain A676. A competitive- ELISA technique based on a competitive pinding between unlabelled protein A and conjugated protein A was employed to measure the concentration of protein A. A study was also conducted to develop this technique. Rabbit IgG was first purified before it was used to coat a microtiterplate. IgG purified using ammonium sulphate precipitation in combination with DEAE-cellulose chromatography gave purer IgG than the caprylic acid method combined with saturated ammonium sulphate or single-step DEAE-cellulose ion exchange chromatography. The molecular weight of the purified IgG was 140,000 dalton based on SDS gelelectrophoresis. The minimum detectable amount of protein A was in the range of 0-20 ng/ml. The optimum concentration of IgG required for coating was 2pg/ml and the incubation time for the substrate was 20 minutes.